Conceptual aspects: analyses law, ethical, human, technical, social factors of development ICT, e-learning and intercultural development in different countries setting out the previous new theoretical model and preliminary findings - Kommers, P.; Smyrnova-Trybulska, E.; Morze, N.; Issa, Theodora; Issa, Tomayess (Inderscience Enterprises Ltd., 2015)
This paper, prepared by an international team of authors focuses on the conceptual aspects: analyses law, ethical, human, technical, social factors of ICT development, e-learning and intercultural development in different countries, setting out the previous and new theoretical model and preliminary findings of study in the framework of the international project IRNet. In particular, the article describes a WP2: analyses of legal, ethical, human, technical and social factors of ICT and e-learning development, and the state of intercultural competences in partner countries. The second part of the paper includes data from preliminary research. During the study and analysis of global (international) and local (national) documents as well as university documents tables were prepared which set forth a comparison of different legal, ethical, human, technical, scientific and social factors of ICT and e-learning development, and the state of intercultural competences in several partner countries, for example the Netherlands, Poland, Ukraine, Australia in the context of the IRNet project – international research network.